Penerapan Manajemen Modern dalam Optimalisasi Pelayanan di Kantor Notaris - komang widhya sedana putra p; I Komang Didi Kariana; Ni Wayan Lasmi; Kadek Wulandari Laksmi P; IGN Oka Ariwangsa (JPM: Jurnal Pengabdian Masyarakat, 2024)
This Community Service Program (PKM) was conducted at Kantor Notaris-PPAT I Putu Setiawan, S.H., M.Kn in Gianyar Regency with the primary goal of enhancing operational efficiency and service quality. The main issues identified included slow and inefficient manual document management and unstructured time management, which negatively impacted administrative processes and client satisfaction. To address these issues, the program implemented two main solutions: digitalizing documents using a technology-based document management system and applying an integrated time management system. Additionally, the program included intensive staff training to ensure effective adaptation to new technologies and managerial methods. Preliminary results indicate a significant improvement in service speed and accuracy, as well as a reduction in administrative errors. The new document management system allows for faster and more structured access, while the time management system aids in prioritizing tasks and managing schedules more effectively. Consequently, the program has successfully enhanced staff productivity and client satisfaction, providing a solid foundation for further development in managerial practices at the notary office.